“Documentality” of the Collection “Dans la Steppe” in S. Persky’s Interpretation - T. G. Maksimova (Научный диалог)
The article is devoted to the analysis of the French collection “Dans la steppe” (1902), compiled and translated by S. M. Persky, which includes the following early stories of M. Gorky: “In the steppe”, “Grandfather Arkhip and Lyonka”, “Song of the Falcon”, “Emelyan Pilyai”, “The Khan and his son”, “Notch”, “Makar Chudra”, “Twenty-six and one”, “Old Woman Izergil”. Attention is paid to the preface of the collection written by Persky, in which he names facts from the life of the writer, thereby justifying the choice of stories and characterizing the main feature of the style of Gorky's early stories, manifested in the synthesis of documentary and artistic, namely, the description of the “autobiographical” space, the component of which is the image of the steppe. The author of the article dwells on the three most exhibitive in this aspect stories: “In the Steppe”, “Grandfather Arkhip and Lyonka”, “Emelyan Pilyai”. The author comes to the conclusion that Persky solves two primary tasks: first, the compiler of the collection acquaints the reader with the facts of Gorky's biography, and secondly, characterizes the author's style reflecting the transformation of the documentary style into the artistic one. It is shown that the collection, which includes stories arranged in a certain sequence, represents a story about the writer's search for his place in life.